Aktulisasi Dir pada Tim Pendamping Keluarga Berdasarkan Riwayat Pendidikan: Bagiamana dengan Dukungan Sosial? - Aulia, Sayidah; Ezer, Eben; Lutfiani , Aisyah; April , Eko; Fitrianawati, Gama Dwi (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
The aim of this research is to clarify the differences between social support and self-actualization. based on the educational story of the stunting Family Support Team in Surabaya City. This research uses a quantitative research model by applying reciprocal or cause and effect research. The total number of subjects was 376 volunteers from the Stunting Family Support Team in Surabaya City. The sample size is based on the Krejcie and Morgan table with a total family support team population of 6,000 members. The data collection procedure uses an online questionnaire using a 5-point Likert scale using Google Forms. The data analysis procedure uses multiple linear regression analysis techniques. Based on the research results, it is proven that there is a significant difference between middle school, high school, diploma and bachelor's education history with a sig.<0.05 value found in the high school education history, while middle school, diploma and bachelor's education history does not show a sig.<0.05. Based on the significance value obtained, there is quite a significant difference between educational history and social support variables on self-actualization